Stem Cell-Derived Oligodendroglial Cells for Therapy in Neurological Diseases. - García-León, Juan Antonio; Verfaillie, Catherine M. (Bentham Science, 2016)
There are an important number of neurological diseases where not neurons but glia are the responsible cells for the degeneration of the nervous system. In the last years, determinant roles for oligodendrocytes (OLs) have been demonstrated not only in myelin generation and maintenance but also for metabolic support of neurons. Oligodendroglial defects lead to brain degeneration in several diseases, supporting the idea that not only endogenous regeneration but also administration of exogenous OL precursors will lead to overcome functional deficits. In this review, we discuss many diseases where OLs play a crucial role, and focus on the different sources and methods to obtain oligodendroglial cells that could be used in cell therapy for myelin-related and oligodendrocyte-deficient diseases.
Keywords: Esclerosis múltiple; multiple sclerosis